Biodegradable lamination material and preparation method thereof

By introducing hyperbranched polyester and nanosilica surface modified hyperbranched polyester into biodegradable coating materials, the problems of material flowability, processing performance and compatibility are solved, and rapid, stable and efficient coating production and excellent mechanical properties and barrier properties are achieved.

CN119708791APending Publication Date: 2025-03-28SHANGHAI YINGHUA CHENRUI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411830827.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing biodegradable coating materials have problems in terms of fluidity, processing performance and compatibility, which makes it difficult to apply uniformly during processing, prone to sticking rollers and breakage, and have poor compatibility, limiting their application scope.

Method used

By introducing hyperbranched polyester and nanosilicon dioxide surface modified hyperbranched polyester, the binding force between resins and the toughness of PLA is improved, and the synergy of suitable formulations is designed to improve the fluidity and compatibility of the coating materials.

Benefits of technology

It realizes rapid production of coating materials, strong stability of membrane surface rupture, good fluidity, easy processing and molding, excellent mechanical properties, good barrier properties and degradation properties, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a biodegradable lamination material and a preparation method thereof. The method comprises the following steps: stirring and mixing PLA (polylactic acid), PBAT (polyethylene terephthalate-co-caprolactone), SiO2-HBPE3 (silicon dioxide grafted hyperbranched polyester) and an auxiliary agent through a high-speed mixer; the preparation method comprises the following steps: uniformly mixing the raw materials, adding the uniformly mixed raw materials into twin-screw extrusion equipment for extrusion, carrying out bracing, traction, cooling and pelletizing processes to prepare PLA coating composite modified particles, treating the modified particles in a vacuum dehumidification box, and finally coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a biodegradable coating material and a preparation method thereof. Background Art

[0002] In recent years, with global warming and the improvement of human environmental awareness, corresponding degradable materials have begun to appear in the field of traditional non-degradable materials, including the field of coating materials. Traditional non-degradable coating materials are mainly polyethylene (PE), which is widely used in disposable paper cups and fast food packaging after being compounded with paper layers. Traditional PE coating materials are gradually developing towards PLA biodegradable coating materials, but at present, the biodegradable coating materials have problems such as thick coating thickness, slow coating speed, and thin neck due to their high density, which also limits the further development of materials in this field. At the same time, due to the high brittleness and poor tear resistance of PLA, it is necessary to modify PLA to obtain a biodegradable coating material with excellent comprehensive performance. Patent CN111719341A discloses a production process of PLA coated paper and its production process. The coating layer used in the patent is a coating liquid coated on the base paper. The coating liquid is obtained by blending thermoplastic starch, plasticizer and PLA. The method involves dissolving all materials and preparing them. The production process and recycling work are relatively cumbersome. Patent CN1398766A discloses a method of compounding PE plastic film and base paper layer by acrylic glue layer. The acrylic acid and PE materials used are not biodegradable materials. After use and discard, they cannot be degraded in nature, causing environmental pollution. Patent CN102558797B discloses a PLA biodegradable coated paper material. The compatibility is improved by adding toughening resin and a certain amount of elastomeric material to PLA. The overall degradation performance of this part of the material has a certain impact during use. In summary, in order to meet environmental challenges, the industry has begun to seek new barrier technologies using bio-based materials. These technologies aim to develop new paper-based packaging materials that are both biodegradable and can maintain the necessary barrier properties. At present, a variety of biodegradable materials have been used in the preparation of coated paper, such as polylactic acid (PLA), polybutylene adipate-terephthalate (PBAT), etc. These materials meet the needs of biodegradation to a certain extent, but there are still some problems in terms of fluidity, processing performance and compatibility with other materials. Some biodegradable materials have poor fluidity in the molten state, which makes it difficult to evenly coat them on the paper surface during processing, affecting the quality and performance of the product; some biodegradable materials are prone to problems such as sticking to the roller and breaking during processing, which increases the difficulty and cost of production; the compatibility between different biodegradable materials is poor, and it is difficult to form a stable blend, which limits its application range in the preparation of coated paper. Therefore, it is particularly important to provide a new biodegradable coating material and its preparation method. Summary of the invention

[0003] The object of the present invention is to provide a biodegradable coating material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] In order to solve the above technical problems, the present invention discloses a biodegradable coating material and a preparation method thereof.

[0005] A biodegradable coating material, comprising the following components by weight:

[0006]

[0007] Furthermore, the PLA structure is one or two or more of the left-handed polylactic acids, with a melt index of 5-30 g / 10 min, preferably Total, LX575, LX530 or L105 series.

[0008] Furthermore, the toughening resin is a biodegradable resin, including one or two or more of polybutylene adipate / terephthalate, polybutylene succinate, polyhydroxyalkanoate, and polycaprolactone, with a melt index of 5-30g / 10min, preferably PBAT of Wanhua Group model T16, and preferably PHA is PHBH BP350 series of Blue Crystal Microbiology Company.

[0009] Furthermore, the preparation method of the silica-modified hyperbranched polyester comprises treating the surface of nano-silica, using p-toluenesulfonic acid as a catalyst, adding (2,2-bis(hydroxymethyl)propionic acid) DMPA to react, and filtering under reduced pressure to obtain the silica-modified hyperbranched polyester.

[0010] Furthermore, the antioxidant is a phenolic antioxidant and / or a phosphite antioxidant, which is one or two or more of antioxidant 1010, antioxidant 168, and antioxidant 1076, preferably antioxidant 1010 and antioxidant 168.

[0011] Furthermore, the compatibilizer is one or two or more of PLA-g-MA, PBAT-g-MA, and PCL-g-MA, preferably PLA-g-MA.

[0012] Furthermore, the lubricant is one or two or more of erucamide, oleamide, and stearamide, preferably erucamide or stearamide.

[0013] Furthermore, the synthesis path of the silica-modified hyperbranched polyester is:

[0014] S1: Add 29.0 g of nano-silica to 290 mL of toluene, stir and shake for 2 h, add 1.16 g of silane coupling agent KH550, heat to 110 ° C, reflux at a constant temperature for 2 h, filter under reduced pressure and wash with anhydrous ethanol, and dry the product in a vacuum oven to obtain surface-treated nano-silica;

[0015] S2: After fully stirring and dispersing 6 g of surface-treated nano-silica and 240 mL of xylene in a flask, add p-toluenesulfonic acid as a catalyst, raise the temperature to reflux temperature of 145°C, and add 2,2-bis(hydroxymethyl)propionic acid in batches after the temperature is constant, adding 1.5 g every 10 minutes. After the addition is completed, keep the temperature constant for 2 hours to allow the modified nano-silica to fully react with DMPA;

[0016] After the reaction, the mixture was filtered under reduced pressure to obtain SiO2-HBPE1. The above steps were repeated three times to obtain SiO2-HBPE2 and SiO2-HBPE3. The number average molecular weight of the third-generation SiO2-HBPE3 was determined by titration to be 4.92×103 and the grafting rate was 48.1%.

[0017] Furthermore, the preparation method of the PLA-g-MA is as follows: based on 100 parts of PLA, 3 parts of maleic anhydride and 0.3 parts of dicumyl peroxide are first dissolved in 30 ml of ethanol, and after the dissolution is complete, the solution is poured into the PLA, mixed evenly, and after the ethanol is volatilized, the mixture is added to an internal mixer for internal mixing and blending, the temperature of the internal mixer is set to 170° C., the internal mixing time is 5 minutes, and after the internal mixing is completed, extrusion granulation is performed through a single screw extruder, and the temperatures from a zone to the head of the extruder are set to 130° C., 145° C., 165° C., 160° C., and 150° C., respectively; finally, the particles are placed in a vacuum oven and dried at 60° C. for 24 hours to obtain PLA-g-MAH.

[0018] In a second aspect, the present invention also provides a method for preparing a biodegradable coating material, characterized in that it comprises the following steps:

[0019] S1: PLA, toughening resin, hyperbranched polyester, and each component resin and auxiliary material are weighed and added into a high-speed mixer for mixing. PLA, toughening resin, and auxiliary materials are mixed in advance in a high-speed mixer at 50-65° C. and 200-400 rpm for 1-5 min. After being evenly mixed, they are added into a twin-screw extruder, melt-extruded, and then drawn out from the outlet of the die head. After cooling and pelletizing, PLA modified coating material composite slice particles are obtained. The melt extrusion temperature of the twin-screw extruder is 150-200° C., and the screw speed is 200-400 rpm.

[0020] S2: Dry the extruded and sliced ​​particles in a dehumidified drying oven at 80-100°C for 4 hours to obtain dry sliced ​​particles with a moisture content of less than 300 ppm, and then add the dried sliced ​​particles into the hopper of a film casting extruder for cast extrusion, with a die head temperature of 210°C-230°C, a barrel temperature of 200-220°C, and a casting speed of 50-150 m / min.

[0021] The structure of silica surface modified hyperbranched polyester is as follows:

[0022]

[0023] Compared with the prior art, the present invention provides a biodegradable coating material and a preparation method thereof, which has the following beneficial effects:

[0024] (1) The present invention introduces hyperbranched polyester into the PLA system coating material. The hyperbranched polyester is a highly branched three-dimensional structure and has a large number of active terminal groups. It can effectively improve the bonding force between resins, and has a toughening effect on PLA, improves the tear strength, solves the problem of easy rupture of the film surface caused by increasing the coating speed, and has good thermal stability at high processing temperatures;

[0025] (2) The present invention designs each formula to synergize under a suitable ratio, so that the PLA biodegradable coating material can be prepared at a fast speed, and at the same time, the film surface rupture stability can be ensured to be strong, thereby improving the efficiency of the preparation process and reducing the preparation cost;

[0026] (3) The biodegradable coating material prepared by the present invention has good fluidity, is easy to process and shape, is not easy to break under tension, has excellent mechanical properties, has good elasticity and plasticity, can maintain integrity under large deformation, has strong ability to resist crack extension and brittle fracture, is not easy to be damaged under bending load, the materials are tightly bonded and the coating weight is large, has better barrier properties, can more effectively prevent the penetration of gas, liquid and microorganisms, thereby protecting the items in the package, and the coating material with a large weight has a relatively large thickness or a high density. The increase in thickness improves the barrier properties of the material, such as oil-proof and waterproof properties, as well as the strength and durability of the material; the coating material with a large weight usually has better mechanical properties, such as tensile strength, tear strength and wear resistance. The improvement of these properties helps the material to withstand greater stress and pressure in applications such as packaging and printing; the biodegradable coating material prepared by the preparation method of the biodegradable coating material of the present invention has excellent processing performance (melt index), mechanical properties (tensile strength, elongation at break, bending strength), toughness (impact strength) and bonding performance (bonding strength) and other aspects;

[0027] (4) The present invention adds nano-silicon dioxide to modify the surface and then performs hyperbranched polymerization. The surface modification of silicon dioxide improves the fluidity of the material system, improves the tear strength of the material under high fluidity, reduces film surface rupture, and the three-dimensional structure formed by the hyperbranched polyester makes the film surface have better strength and toughness during high-speed lamination, thereby overcoming the problem of slow lamination rate of conventional PLA laminating materials;

[0028] (5) After the silicon dioxide is surface treated, the overall fluidity of the material is improved, the coating production efficiency is improved, and the gram weight is reduced, thereby achieving the effect of reducing costs and increasing efficiency for enterprises;

[0029] (6) The silica surface-modified grafted hyperbranched polyester resin in the biodegradable coating material prepared by the present invention has a large number of active groups at its end, forming a dense structure with other components, reducing the processing degradation behavior of the material at higher temperatures and improving the process stability. DETAILED DESCRIPTION

[0030] Further embodiments of the present invention are described below. It should be understood that the further embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] In addition, in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes, and do not specifically refer to the order or sequence, nor are they used to limit the present invention. They are only used to distinguish components or operations described with the same technical terms, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions and technical features between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0032] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are analytical reagents (AR) unless otherwise specified. Parts are parts by weight unless otherwise specified, and the materials are purchased from commercial channels.

[0033] Example 1

[0034] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PBAT, SiO2-HBPE3 and the additives were stirred at 60°C and 300rpm for 3min in a high mixer to mix evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The modified particles were placed in a vacuum dehumidification box at 100°C for 4h, and then coated by a cast film coating machine. The coating temperature was 190 / 200 / 205 / 210 / 210 / 215 / 215 / 220°C, the die temperature was 225°C, and the coating rate was 150m / min.

[0035] Embodiment 2:

[0036] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PHA, SiO2-HBPE3 and the additives were stirred in a high-speed mixer at 60°C and 300rpm for 3 minutes to mix them evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0037] Embodiment 3:

[0038] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PBAT, SiO2-HBPE3 and the additives were stirred in a high mixer at 60°C and 300rpm for 3min to mix evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0039] Embodiment 4:

[0040] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PHA, SiO2-HBPE3 and the additives were stirred in a high-speed mixer at 60°C and 300rpm for 3 minutes to mix them evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0041] Embodiment 5:

[0042] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PBAT, SiO2-HBPE3 and the additives were stirred in a high mixer at 60°C and 300rpm for 3min to mix evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0043] Comparative Example 1:

[0044] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA and antioxidant were stirred in a high-speed mixer at 60°C and 300 rpm for 3 minutes to be evenly mixed, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250 rpm. After the twin screws were melted, they were extruded, and after drawing, traction, cooling, and pelletizing, PLA coated composite modified particles were obtained. The coating steps were the same as those in Production Process Example 1.

[0045] Comparative Example 2:

[0046] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PBAT and the additives were stirred in a high-speed mixer at 60°C and 300rpm for 3min to mix evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin screws were melted, they were extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0047] Comparative Example 3:

[0048] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PHA, SiO2-HBPE3 and the additives were stirred in a high-speed mixer at 60°C and 300rpm for 3 minutes to be evenly mixed, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0049] Comparative Example 4:

[0050] The raw materials were prepared according to the components of Example 1 shown in Table 1. PLA, PHA, SiO2-HBPE3 and the additives were stirred in a high-speed mixer at 60°C and 300rpm for 3 minutes to be evenly mixed, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted, it was extruded, and after drawing, traction, cooling and pelletizing, PLA coated composite modified particles were obtained. The coating step was the same as that in Production Process Example 1.

[0051] Table 1: Examples and Comparative Examples

[0052]

[0053] Table 2: Performance test results of examples and comparative examples

[0054]

[0055] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A biodegradable coating material, characterized in that: By mass, it includes the following components:

2. The biodegradable coating material according to claim 1, characterized in that: The PLA structure is one or two or more of the left-handed polylactic acids, with a melt index of 5-30 g / 10 min, preferably Total, LX575, LX530 or L105 series.

3. The biodegradable coating material according to claim 1, characterized in that: The toughening resin is a biodegradable resin, including one or two or more of polybutylene adipate / terephthalate, polybutylene succinate, polyhydroxyalkanoate, and polycaprolactone, with a melt index of 5-30g / 10min, preferably PBAT of Wanhua Group model T16, and preferably PHA is PHBH BP350 series of Blue Crystal Microbiology Company.

4. The biodegradable coating material according to claim 1, characterized in that: The preparation method of the silica-modified hyperbranched polyester comprises treating the surface of nano-silicon dioxide, using p-toluenesulfonic acid as a catalyst, adding (2,2-bis(hydroxymethyl)propionic acid) DMPA for reaction, and filtering under reduced pressure to obtain the silica-modified hyperbranched polyester.

5. The biodegradable coating material according to claim 1, characterized in that: The antioxidant is a phenolic antioxidant and / or a phosphite antioxidant, which is one or two or more of antioxidant 1010, antioxidant 168, and antioxidant 1076, preferably antioxidant 1010 and antioxidant 168.

6. The biodegradable coating material according to claim 1, characterized in that: The compatibilizer is one or two or more of PLA-g-MA, PBAT-g-MA, and PCL-g-MA, preferably PLA-g-MA.

7. The biodegradable coating material according to claim 1, characterized in that: The lubricant is one or two or more of erucamide, oleamide, and stearamide, preferably erucamide or stearamide.

8. The biodegradable coating material according to claim 4, characterized in that: The synthesis path of the silica-modified hyperbranched polyester is: S1: Add 29.0 g of nano-silica to 290 mL of toluene, stir and shake for 2 h, add 1.16 g of silane coupling agent KH550, heat to 110 ° C, reflux at a constant temperature for 2 h, filter under reduced pressure and wash with anhydrous ethanol, and dry the product in a vacuum oven to obtain surface-treated nano-silica; S2: After fully stirring and dispersing 6 g of surface-treated nano-silica and 240 mL of xylene in a flask, add p-toluenesulfonic acid as a catalyst, raise the temperature to reflux temperature of 145°C, and add 2,2-bis(hydroxymethyl)propionic acid in batches after the temperature is constant, adding 1.5 g every 10 minutes. After the addition is completed, keep the temperature constant for 2 hours to allow the modified nano-silica to fully react with DMPA; After the reaction, the vacuum was filtered to obtain SiO2-HBPE1. The above steps were repeated three times to obtain SiO2-HBPE2 and SiO2-HBPE3. The number average molecular weight of the three generations of SiO2-HBPE3 was determined by titration to be 4.92×10 3 , grafting rate 48.1%.

9. The biodegradable coating material according to claim 6, characterized in that: The preparation method of the PLA-g-MA is as follows: based on 100 parts of PLA, 3 parts of maleic anhydride and 0.3 parts of dicumyl peroxide are first dissolved in 30 ml of ethanol, after the dissolution is complete, the solution is poured into the PLA, mixed evenly, and after the ethanol is volatilized, the mixture is added to an internal mixer for internal mixing and blending, the temperature of the internal mixer is set to 170° C., the internal mixing time is 5 minutes, after the internal mixing is completed, extrusion granulation is performed through a single screw extruder, and the temperatures from a zone to a head of the extruder are set to 130° C., 145° C., 165° C., 160° C., and 150° C., respectively; finally, the particles are placed in a vacuum oven and dried at 60° C. for 24 hours to obtain PLA-g-MAH.

10. The method for preparing the biodegradable coating material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: PLA, toughening resin, hyperbranched polyester, and each component resin and auxiliary material are weighed and added into a high-speed mixer for mixing. PLA, toughening resin, and auxiliary materials are mixed in advance in a high-speed mixer at 50-65° C. and 200-400 rpm for 1-5 min. After being evenly mixed, they are added into a twin-screw extruder, melt-extruded, and then drawn out from the outlet of the die head. After cooling and pelletizing, PLA modified coating material composite slice particles are obtained. The melt extrusion temperature of the twin-screw extruder is 150-200° C., and the screw speed is 200-400 rpm. S2: Dry the extruded and sliced ​​particles in a dehumidified drying oven at 80-100°C for 4 hours to obtain dry sliced ​​particles with a moisture content of less than 300 ppm, and then add the dried sliced ​​particles into the hopper of a film casting extruder for cast extrusion, with a die head temperature of 210°C-230°C, a barrel temperature of 200-220°C, and a casting speed of 50-150 m / min.

Citation Information

Patent Citations

  • Biodegradable PE-coated paper material and preparation method thereof

    CN102558797B

  • PLA coated paper and production process thereof

    CN111719341A

  • Composite packing paper and its production process

    CN1398766A

  • Biodegradable PE-coated paper material and preparation method thereof

    CN102558797A

  • Preparation method of modified polybutylene succinate composite material for sensor shell

    CN109880312A

Cited By

  • Polycarbonate lamination material with high sealing strength

    CN120331059A

  • A polycarbonate laminated material with high seal strength

    CN120331059B